ORGANIC MATTER CONTENT IN SOIL UNDER COCOA PLANTS IN LOWLANDS AND HIGHLANDS - Mowidu, Ita; Soande, Yehezkiel; Nurulazmi, Aqiqah (Agropet, 2025)
Soil organic matter is an important factor that determines soil fertility and health. This is very important for plant growth, development and yield. Elevation influences the climate elements of a region and subsequently influences the decomposition of organic matter, and then affects the decomposition of organic materials. This study aims to determine the organic material content in the soil under cocoa plants in the lowlands and highlands. The amount of organic matter content in the soil can be predicted from the results of the C-organic content analysis, namely by multiplying the C-organic content by a constant as a correction factor, namely 1.724. The organic C content was determined from composite soil samples taken at 10 sites at each location starting from the surface soil to a depth of approximately 20-30 cm. The results of the study showed that in the same area, the soil organic matter content was higher on slopes (3.84% in lowlands and 4.62% in highlands) where the soil surface was covered with litter compared to valleys (1.48% in lowlands and 2.6% in highlands) which were surface water flow areas. Furthermore, in areas with the same landscape (slopes or valleys), the soil organic matter content is higher in the highlands (4.62% on slopes and 2.6% in valleys) compared to the lowlands (3.84% on slopes and 1.48% in valleys).